[RETRACTED] : Peranan INCAR (Informasi Cerdas Ala Remaja) Dalam Program GenRe (Generasi Berencana) di Kabupaten Nunukan - Aziza, Tri Noor; Itcianday, Itcianday (Jurnal Borneo Administrator, 2018)
Retracted Following a rigorous and careful concerns and consideration in the review of the article published in Jurnal Borneo Administrator entitled â€œPeranan â€œINCARâ€ (Informasi Cerdas Ala Remaja) dalam Program Genre (Generasi Berencana) di Kabupaten Nunukanâ€ Vol. 14, No. 3, pp. 171-188, Desember 2018, DOI: http://doi.org/10.24258/jba.v14i3.364. This paper has been found to violate the principles of Jurnal Borneo Administrator Publication and has been retracted. The article has contained redundant material and throughout a careful examination, the editor has found that the paper has also been published in Jurnal Kesejahteraan Keluarga dan Pendidikan, Vol. 5, No. 2, pp. 126-138, Oktober 2018, DOI: http://dx.doi.org/10.21009/JKKP.052.04. The document and its content have been removed from Jurnal Borneo Administrator, and reasonable effort should be made to remove all references to this article.